2020
DOI: 10.1007/s00415-020-09973-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with employment and expected work retention among persons with multiple sclerosis: findings of a cross-sectional citizen science study

Abstract: Background Multiple sclerosis (MS) notably affects adults of working age. For persons with MS (PwMS), being employed enhances their quality of life and it may be regarded as an indicator of overall functioning. Thus, ensuring work participation in PwMS is of general public health interest. Objective To examine relevant socio-demographic, MS-, health- and work-related factors, including psychosocial working conditions, associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
0
14
1
Order By: Relevance
“…Austria [ 39 ], Czech Republic [ 40 ], Greece [ 41 ], Hungary [ 42 ], Kuwait [ 43 ], Portugal [ 44 ], Russia [ 45 ], and Argentina [ 46 ] each contributed with one (0.6%) publication reporting the prevalence of unemployed subjects. Ireland [ 47 , 48 ], Israel [ 49 , 50 ], Poland [ 51 , 52 ], and Saudi Arabia [ 53 , 54 ] contributed with two (1.3%) studies each while Brazil [ 55 57 ], Iran [ 58 – 60 ], Holland [ 61 63 ], Norway [ 11 , 64 , 65 ], and Switzerland [ 66 68 ] contributed with three (2.0%) studies each. Most of the data on the estimates of the prevalence comes from Canada (four, 2.6%) [ 69 – 72 ], Denmark (five, 3.3%) [ 73 77 ], Belgium (five, 3.3%) [ 35 , 78 81 ], France (five, 3.3%) [ 82 86 ], Spain (five, 3.3%) [ 8 , 28 , 33 , 87 , 88 ], Sweden (seven, 4.6%) [ 89 95 ], Germany (eight, 5.3%) [ 96 103 ], Australia (eight, 5.9%) [ 38 , 104 110 ], Italy (nine, 5.9%) [ 111 …”
Section: Resultsmentioning
confidence: 99%
“…Austria [ 39 ], Czech Republic [ 40 ], Greece [ 41 ], Hungary [ 42 ], Kuwait [ 43 ], Portugal [ 44 ], Russia [ 45 ], and Argentina [ 46 ] each contributed with one (0.6%) publication reporting the prevalence of unemployed subjects. Ireland [ 47 , 48 ], Israel [ 49 , 50 ], Poland [ 51 , 52 ], and Saudi Arabia [ 53 , 54 ] contributed with two (1.3%) studies each while Brazil [ 55 57 ], Iran [ 58 – 60 ], Holland [ 61 63 ], Norway [ 11 , 64 , 65 ], and Switzerland [ 66 68 ] contributed with three (2.0%) studies each. Most of the data on the estimates of the prevalence comes from Canada (four, 2.6%) [ 69 – 72 ], Denmark (five, 3.3%) [ 73 77 ], Belgium (five, 3.3%) [ 35 , 78 81 ], France (five, 3.3%) [ 82 86 ], Spain (five, 3.3%) [ 8 , 28 , 33 , 87 , 88 ], Sweden (seven, 4.6%) [ 89 95 ], Germany (eight, 5.3%) [ 96 103 ], Australia (eight, 5.9%) [ 38 , 104 110 ], Italy (nine, 5.9%) [ 111 …”
Section: Resultsmentioning
confidence: 99%
“…For people with a chronic disease in general and for pwMS in particular, however, there is lack of theory‐driven research that explains turnover. A recent study indicated the major role of job resources and job demands in expected work retention, even when considering other potential predictors (such as socio‐demographic, health‐, MS‐, and other work‐related factors) (Lehmann et al., 2020). However, this study remained exploratory, and a deeper understanding of the mechanisms on expected work retention among pwMS is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Women and older persons with MS are more likely to be unemployed. 34 They are also more likely to file an allegation of discrimination. 35 By contrast, an Australian study found no differences in employment discrimination regarding gender or age.…”
Section: Resultsmentioning
confidence: 99%
“…Both female gender and higher age were negatively associated with employment. 34 Women and older persons with MS were also more likely to experience discrimination. 35 The results were in line with research on age-related employment discrimination among the general population, where older persons and especially older women received fewer callbacks from employers with vacancies in various occupations.…”
Section: Discussionmentioning
confidence: 99%